2008
DOI: 10.1001/jama.300.11.1353
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Risk of Metabolic Disorders

Abstract: See also p 1303.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(86 citation statements)
references
References 18 publications
0
85
0
1
Order By: Relevance
“…Furthermore, some persistent organic pollutants (POPs) have been reported to be linked to the prevalence of type 2 diabetes and insulin resistance . Remarkably, there exists an epidemiological link between BPA concentration in urine and type 2 diabetes, cardiovascular disease and liver enzyme abnormalities in a representative sample of adult US population (Lang et al, 2008;vom Saal & Myers, 2008).…”
Section: E2 and Bpa Are Equally Effective Through A Non-classical Estmentioning
confidence: 99%
“…Furthermore, some persistent organic pollutants (POPs) have been reported to be linked to the prevalence of type 2 diabetes and insulin resistance . Remarkably, there exists an epidemiological link between BPA concentration in urine and type 2 diabetes, cardiovascular disease and liver enzyme abnormalities in a representative sample of adult US population (Lang et al, 2008;vom Saal & Myers, 2008).…”
Section: E2 and Bpa Are Equally Effective Through A Non-classical Estmentioning
confidence: 99%
“…Several investigators found that higher BPA concentrations were associated with cardiovascular diagnoses (Lang et al 2008;vom Saal and Myers 2008;Melzer et al 2010) and incident coronary artery disease (Melzer et al 2012). In addition, Asano et al (2010) reported that BPA in the micromolar range activates Maxi-K (KCa1.1) ion channels in human coronary smooth muscle cells in culture to a degree sufficient to hyperpolarize the membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…The ester bonds in BPA-based polymers are subject to hydrolysis and, therefore, BPA leaches into food and drinks from their storage containers. Heat and/or acids speed up the leaching process, and repeated washing of polycarbonate products have all been shown to result in an increase in the rate of leaching of BPA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA) has been well characterized as an endocrine disruptor which can mimic the body's own hormones [1,2], potentially leading to reproductive defects, cancer, obesity and diabetes [2,3]. BPA is a key monomer and plasticizer in the production of epoxy resins and polycarbonate plastic.…”
Section: Introductionmentioning
confidence: 99%